Are health assets associated with improved outcomes for hospitalised older adults? A systematic review. (November 2016) - Gregorevic, Kate J.; Lim, Wen Kwang; Peel, Nancye M.; Martin, Ruth S.; Hubbard, Ruth E.
Highlights: Health assets are protective factors which support health and wellbeing, rather than risk factors that are associated with disease. Many risk factors for adverse outcomes have been identified for hospitalised older adults. Health assets are associated with improved outcomes for hospitalised older adults. This review highlights the need for further research on the effect of health assets in hospitalised older adults. Abstract: Objective: Health assets are protective factors that support health and wellbeing, rather than risk factors that are associated with disease. This concept was developed in the community setting. In hospitalised older adults, the dominant approach has been to identify risk factors, with little examination of health assets. The purpose of this systematic review was to determine whether, in hospitalised older people, individual health assets decrease the risk of post hospital mortality, functional decline, new need for residential care, readmission or longer length of stay. Methods: MEDLINE, EMBASE, CINAHL and PsycINFO were searched to identify studies examining outcomes for hospitalised older adults. Included studies examined at least one potential individual health asset, which was a psychosocial characteristic or health characteristic. Study quality was assessed, and findings are narratively described. Results: Nine prospective cohort and two retrospective cohort studies were identified. subjective, functional and biological health assets were identified. Health assets were associated with decreased risk of post-hospital mortality, functional decline, new need for residential care and readmission. Conclusion: The complex interplay between health status and psychological and social factors is incompletely understood. Health assets are associated with improved outcomes for hospitalised older adults. The small number of studies suitable for inclusion indicates the need for further research in this area.